Variation in the vulnerability of mice expressing human superoxide dismutase 1 to prion-like seeding: a study of the influence of primary amino acid sequence - Jacob I. Ayers; Guilian Xu; Kristy Dillon; Qing Lu; Zhijuan Chen; John Beckman; Alma K. Moreno-Romero; Diana L. Zamora; Ahmad Galaleldeen; David R. Borchelt (Acta Neuropathologica Communications, 2021)
Abstract Misfolded forms of superoxide dismutase 1 (SOD1) with mutations associated with familial amyotrophic lateral sclerosis (fALS) exhibit prion characteristics, including the ability to act as seeds to accelerate motor neuron disease in mouse models. A key feature of infectious prion seeding is that the efficiency of transmission is governed by the primary sequence of prion protein (PrP). Isologous seeding, where the sequence of the PrP in the seed matches that of the host, is generally much more efficient than when there is a sequence mis-match. Here, we used paradigms in which mutant SOD1 seeding homogenates were injected intraspinally in newborn mice or into the sciatic nerve of adult mice, to assess the influence of SOD1 primary sequence on seeding efficiency. We observed a spectrum of seeding efficiencies depending upon both the SOD1 expressed by mice injected with seeds and the origin of the seed preparations. Mice expressing WT human SOD1 or the disease variant G37R were resistant to isologous seeding. Mice expressing G93A SOD1 were also largely resistant to isologous seeding, with limited success in one line of mice that express at low levels. By contrast, mice expressing human G85R-SOD1 were highly susceptible to isologous seeding but resistant to heterologous seeding by homogenates from paralyzed mice over-expressing mouse SOD1-G86R. In other seeding experiments with G85R SOD1:YFP mice, we observed that homogenates from paralyzed animals expressing the H46R or G37R variants of human SOD1 were less effective than seeds prepared from mice expressing the human G93A variant. These sequence mis-match effects were less pronounced when we used purified recombinant SOD1 that had been fibrilized in vitro as the seeding preparation. Collectively, our findings demonstrate diversity in the abilities of ALS variants of SOD1 to initiate or sustain prion-like propagation of misfolded conformations that produce motor neuron disease.